Nutraceuticals and human blood platelet function : applications in cardiovascular health - Duttaroy, Asim K. (Hoboken, NJ : Wiley, 2018)
'A comprehensive review of the impact of dietary nutraceuticals on platelet function and its relationship to cardiovascular disease'--Provided by publisher.
Human blood platelets and their role in the development of cardiovascular disease -- Epidemiology of cardiovascular disease -- N-2 fatty acids and human platelets -- Effects of garlic, onion, ginger and tumeric on platelet function -- Herbs and platelet function -- Tomato extract and human platelet function -- Dietary nitrates and their antiplatelet effects -- Kiwifruit and human platelet function -- Polyphenols and human platelets -- Effects of ginkgo biloba, ginseng green tea, and dark chocolate on human blood platelet function -- Plant alkaloids and platelet function -- Strawberries and human platelet function -- Effects of metal ions on platelet function -- Individual compounds isolated from plant sources with anti-platelet activity.
Includes bibliographical references and index.
Keywords: Cardiovascular Diseases -- prevention & control; Cardiovascular Diseases -- etiology; Dietary Supplements; Functional Food; Platelet Activation -- physiology